Ciprofloxacin Dosage and Emergence of Resistance in Human Commensal Bacteria - Fantin, Bruno; Duval, Xavier; Massias, Laurent; Alavoine, Loubna; Chau, Françcoise; Retout, Sylvie; Andremont, Antoine; Mentré, France (The Journal of infectious diseases, 2009)
Background Although optimization of the fluoroquinolone dosage increases the efficacy of this class of drugs against bacterial infections, its impact on the emergence of resistance in commensal bacteria is unknown. Methods Six different 14-day dosages of oral ciprofloxacin were randomly assigned to 48 healthy volunteers. Individual pharmacokinetic and pharmacodynamic parameters combining antibiotic exposure in plasma, saliva, and stool specimens and ciprofloxacin minimum inhibitory concentrations (MICs) and mutant prevention concentrations against viridans group streptococci in the pharyngeal flora and Escherichia coli in the fecal flora were estimated. Their links with the emergence of resistance to nalidixic acid or ciprofloxacin in the fecal flora and to levofloxacin in the pharyngeal flora 7, 14, or 42 days after ciprofloxacin initiation were investigated. Results Resistance emerged in the fecal and pharyngeal flora of 25% and 33% of the subjects, respectively, mainly when local concentrations of ciprofloxacin were less than the MIC. No variable that integrated pharmacokinetic data and pharmacodynamic parameters was found to differ significantly between the subjects in whom resistance emerged and those in whom it did not. Probabilities of the emergence of resistance were not significantly different across the different antibiotic dosages. Conclusions Selection of resistant commensals during ciprofloxacin therapy is a frequent ecological side effect that is not preventable by dosage optimization. Trial registration Clinical Trials.gov identifier: NCT00190151.